Persistent Eosinophilia and Fever in Pancreatitis: A Clinical Conundrum - John Noel MD; Abbott Fields MD; Arrouk Rami MD; Sharma Nirupma MD (SAGE Publishing, 2022)
A healthy 11-year-old girl presents with epigastric abdominal pain, fever, weight loss, and decreased appetite for 1 month. On physical examination, she appears ill, dehydrated, and cachectic. Her abdominal examination is significant for large ascites with a fluid wave and is nontender to palpation. Her labs show leukocytosis with an eosinophilic-predominant granulocytosis and an absolute eosinophil count of 6800/mm 3 . She has elevated serum inflammatory markers, hypoalbuminemia, and lipase is 5000 U/L. Magnetic resonance cholangiopancreatography (MRCP) shows an irregular and dilated pancreatic duct, so she had an endoscopic retrograde cholangiopancreatography with pancreatic stent placement, paracentesis, and colonoscopy. Her peritoneal fluid was significant for an eosinophilic-predominant granulocytosis with no evidence of malignancy on flow cytometry. All other studies and cultures did not reveal an etiology. She initially showed improvement, 18 days later she developed a fever, night sweats, tachycardia, and abdominal distention. Empiric antibiotics were initiated due to concern for infected pancreatic necrosis versus spontaneous bacterial peritonitis. Repeat MRCP showed interval development of 2 peripancreatic fluid collections and re-accumulation of ascites. She continued to have daily fever ranging from 39°C to 40°C. Repeat paracentesis and evaluation of her peritoneal fluid showed resolution of eosinophilia with an elevated neutrophil count, negative Gram stain, and no growth on culture. She completed a 10-day course of antibiotics, however, remained febrile with elevated inflammatory markers and leukocytosis throughout her hospitalization. A genetic panel to evaluate for a hereditary cause of chronic pancreatitis was sent and returned positive for a mutation of the serine protease inhibitor Kazal type 1.